Comparative histology and histochemistry of the parotid and sublingual glands in the white-eared opossum (Didelphis albiventris) - Farha, Aline Herrera [UNESP]; de Castro Sasahara, Tais Harumi [UNESP]; Gomes, Silvio Pires [UNESP]; Martins, Leandro Luís; Inamassu, Letícia Rocha [UNESP]; Schimming, Bruno Cesar [UNESP] (Springer Nature, 2025)
The present study aimed to investigate the histology and conventional histochemistry of the parotid and sublingual salivary glands in the Brazilian marsupial known as white-eared opossum. Five adult male white-eared opossums (Didelphis albiventris) were used in this study. Histological and histochemical features of the glands were studied using haematoxylin and eosin, Masson’s Trichrome, Periodic acid-Schiff (PAS) and Alcian blue (AB) (pH = 2.5). The parotid and sublingual glands were surrounded by a connective tissue capsule that delimited the glandular parenchyma. The parotid gland had a parenchyma formed exclusively by serous acini. The parenchyma of the sublingual gland was formed mainly by mucous acini surrounded or covered by serous demilune. The parotid and sublingual glands had the same types of ducts that transported the secretion produced by the secretory acini. The histochemical results in the present study revealed that the parotid gland secretion maybe may contain little bit contents of neutral mucins, and it did not contain acidic mucins, and the sublingual gland secretion may contain neutral and acidic mucins. In conclusion, if we compare the histological findings of this study with previous reports in other American marsupials such as the North American opossum and brush-tailed opossum, it can be suggested that the parotid and sublingual glands do not present morphological differences at light microscopy level, although they are marsupials with similar eating habits but living in environments with different climatic characteristics or with different eating habits, respectively.
Keywords: Acini; Histology; Marsupials; Mucins; Possums; Salivary glands